Stress Factors and Job Performance of Lecturers in Tertiary Institutions in Nigeria - Annabel .U. Obinna-Akakuru; Uzoma B. Njoku; Victoria Chinwendu Agunanne; Ezinne Nelson-Okata; Onyinyechi I. Onwujialiri (International Journal of Education, Teaching, and Social Sciences, 2022)
This study examined stress factors on job performance of lecturers in Imo State. Nigeria. Six specific purposes, six research questions and six hypotheses guided the work. The study employed inferential survey research design. The population of this study consisted of all lecturers in the tertiary institutions in Imo state which are eight thousand, three hundred (8,300). The sample size for this is 382, determined using the Taro Yamane formula. The researcher applied a random sampling technique to ensure that all selected groups have an equal chance with the other sample that is not selected. The instrument for data collection is a structured questionnaire tagged “Stress as a factor of Job Performance of Lecturers’’. The validity of the research instrument was determined by two specialists in Health Education and one specialist in Educational Measurement and Evaluation, from Alvan Ikoku FCE Owerri and Imo State University Owerri, respectively, while the reliability coefficient over time of the instrument for data collection was established through test retest method of Pearson product moment correlation coefficient (PPMCC) statistics which gave a reliability coefficient of 0.94. The research questions were answered using, mean, and standard deviations presented in tables, while the hypotheses were tested using t-test statistics at 0.05 level of significance. Findings indicated amongst others that physical, psychological and psycho-social stressors are factors on job performance of lecturers in tertiary institutions in Imo State. Based on the findings, some recommendations were made, which includes amongst others that there is a need to create recreational activities for lecturers to ease job stress. Also, Seminars, workshops and conferences on occupational health services should be organized periodically for lecturers so as to improve their knowledge on occupational stress and related issues.